Scattering and fusion reaction dynamics of O + Zr system around Coulomb barrier. (1st December 2022) - Dash, C.; Swain, R. R.; Tripathy, G.; Naik, I.; Sahu, B. B.
Abstract: A partial wave scattering matrix for the total effective complex potential of nucleus nucleus collisions is proposed to easily analyze the angular variations of elastic scattering and fusion cross-sections simultaneously with a unique potential. The expectation value of the imaginary part of the potential calculated using the distorted waves from the full potential in the elastic channel accounts for . This is equated to the sum of the cross-sections due to absorption in different regions of the potential where the imaginary part is actively present. The potential is taken as energy independent and features a weakly absorbing nature, which supports the resonance states in various partial wave trajectories. Therefore, these resonances show oscillatory behavior changes with respect to energy . In this paper, we discuss elastic scattering and fusion cross-sections in conjunction with the results of for the system.